The Integration of Augmented Reality and Virtual Laboratory based on the 5E Model and Vark Assessment: A Conceptual Framework - Purwaningtyas, D. A.; Prabowo, H.; Napitupulu, T. A.; Purwandari, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Engineering education in aviation vocational education builds up skills and attitudes. Students must deal with the laboratory complexity, especially in radar training. Students must understand so much basic knowledge and enhance their skills. The high equipment cost and inflexibility of current learning make radar training less effective and cognitive. Augmented Reality (AR) integrated with laboratory activities is an opportunity to improve learning outcomes for vocational education training in an online learning platform. This study aims to find student learning problems in radar training and propose a framework for integrating virtual radar laboratories with Augmented Reality. This research used a descriptive analysis approach and a literature study. A survey at four Aviation Polytechnics in Indonesia results in cognitive load and troubleshooting skills as the main problem in radar training. The proposed framework concept for laboratory integration with Augmented Reality is added a learning style: the VARK framework and Augmented Reality design with a 5E-based model to make laboratory interaction design. Virtual laboratory integration with Augmented Reality with learning style proposed to enhance laboratory activity to achieve the troubleshooting capability on radar laboratory and make this learning more flexible and personalized.